Health examinations of child migrants in Europe: screening or assessment of healthcare needs? - Anders Hjern; Liv Stubbe Østergaard; Marie-Louise Nörredam (BMJ Publishing Group, 2019)
Background More than 800 000 asylum-seeking children were registered in Europe during 2015-2017. Many of them arrived with accumulated needs of healthcare. In this study, we examined the legislation for health examinations on arrival for migrant children in the EU/EAA area.Methods We did a survey to child health professionals within the EU-funded MOCHA project, supplemented by desktop research of official documents.Results In all but three surveyed countries in the EU/EEA, there were systematic health examinations of newly settled migrant children. In most eastern European countries and Germany, this health examination was mandatory; while in the rest of western and northern Europe it was mostly voluntary. All countries that had a mandatory policy of health examinations screened for communicable diseases to protect the host population. Almost all countries with a voluntary policy also aimed to assess a child's individual healthcare needs, but this was rarely the case in countries with a mandatory policy.Conclusion Systematic health examinations of migrant children are routinely performed in most countries in the EU/EEA; but in many countries, it could be improved considerably by extending the focus from screening for communicable diseases to assessing and addressing individual needs of healthcare.